Patterns of use of periodical literature in the Mindanao State University Library its implications to the serial services program - Fernandez, Meles C., 1952-
A stratified random sample of 126 MSU faculty, researchers and senior students from twelve MSU colleges in Marawi City constitute the respondents of the study. Out of the 126 respondents, two students were not library users while twenty (15 students and five faculty members) were not periodical literature users during the given school term.